Jamaica. Significant achievements 2010-2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Jamaica are identified, during the period from 2010 to 2017, with respect to the needs and interests of the country, strengthening issues such as good practices, exports, fodder planting, product storage, sustainability, use of greenhouses, beekeeping, product packaging, animal nutrition, genetics, resilience against climate change, pest control and in the management of diseases, such as coffee rust. Likewise, work was done to improve the value chains of sweet potatoes, coffee, ruminants, fish and high-quality planting. Finally, support is given to small and medium-sized companies.